Analyzing The Effect of Financial Ratio on Financial Distress Using The Logistic Regression Method in Manufacturing Companies - Putri, Windi Marnizal; Irsan, Maria Yus Trinity (Journal of Actuarial, Finance, and Risk Management, 2024)
Financial distress is a company that has difficulty paying its obligations, so it cannot carry out business as usual and may experience bankruptcy. This study aims to analyse the factors that influence the possibility of financial distress by considering financial ratios as indicators to predict the occurrence of financial distress in manufacturing companies in Indonesia. Four independent variables which are financial ratios include Current Ratio, Debt Ratio, Return on Assets (ROA), and Working Capital Turnover. In comparison, the dependent variable is financial distress. This study uses the Altman Z-score model and the data analysis method used is logistic regression analysis. Where logistic regression is one of the statistical analysis methods used to represent the relationship between independent variables and dependent variables containing nominal and ordinal data. The population used in this study includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The sample was determined by the purposing sampling technique. The results showed that not all financial ratios can have a significant effect on the occurrence of Financial Distress. In the results that have been analysed, it is found that Current Ratio does not have a significant positive effect on Financial Distress, Debt Ratio does not have a significant effect on Financial Distress, Return on Assets (ROA) has a significant positive effect on Financial Distress, and the last financial ratio Working Capital Turnover has a significant negative effect on Financial Distress.